Sosial Media Instagram sebagai Sarana Eksistensi Diri pada Mahasiswa Ilmu Komunikasi Angkatan 2021 Universitas Mulawarman - Haikal, Muhammad Fikri; Alfiando, Johantan (SENTRI: Jurnal Riset Ilmiah, 2025)
This study explores the role of Instagram as a medium for self-existence among Communication Science students of Mulawarman University class of 2021. Using a qualitative approach, this research examines how students utilize Instagram to build their identities, strengthen self-confidence, and obtain social recognition in the digital era. The findings indicate that Instagram features such as photo and video uploads, likes, and comments become the main instruments for expressing self-existence and constructing a desired self-image. Through these features, students can shape and present versions of themselves that reflect how they want to be viewed by others. Instagram allows them to share achievements, lifestyle choices, and personal interests as part of their identity performance. The study also finds that such activities often help students gain appreciation from peers, expand their social networks, and enhance their sense of belonging within online communities. However, the use of Instagram is not without negative implications, as it can generate social pressure to appear perfect, create anxiety due to constant comparison with others, and lead to dependence on validation from likes and comments. Despite these challenges, Instagram remains a significant platform for self-expression, creativity, and interaction. Overall, this study concludes that Instagram functions not only as a social networking site but also as a space for identity construction and digital self-affirmation in modern communication practices.